(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2023)
The ocean consists of versatile domain of lives which can be exploited for human health benefits because of diversified secondary metabolites. Seaweeds, generally called macroalgae, are commonly found in the coastal region of the Bay of Bengal. But none of them were investigated properly for their biological activities. Hence, this study was performed to investigate the antioxidant, antimicrobial, cytotoxic and membrane stabilizing activities along with total phenolic content of the crude methanolic extract of three seaweeds namely, Enteromorpha intestinalis, Rhizoclonium riparium and Ceratophyllum demersum using standard protocols. Among the methanolic extracts of three seaweeds, C. demersum (52.09 ± 1.30 mg of GAE) was found to have the highest phenolic content, followed by E. intestinalis (35.98 ± 1.27 mg of GAE) and then R. riparium (29.94 ± 0.54 mg of GAE). The extractives of these seaweeds also showed promising antioxidant and membrane stabilizing properties compared to the standard. E. intestinalis extract displayed greater reducing power with increasing concentration (EC50 value 7.70 ± 0.27 μg/ml). The same seaweed E. intestinalis was found to have significant free radical (DPPH) scavenging potential (IC50 value 23.46 ± 0.54 μg/ml) compared to the reference standard ascorbic acid (IC50 value 5.76 ±0.13 μg/ml). However, the findings of antimicrobial activity test demonstrated mild antibacterial effects of these seaweeds against Escherichia coli and Aspergillus niger and none of these seaweeds exhibited cytotoxicity when tested against HeLa cell line. These findings will aid in future studies attempting to explore medicinal and therapeutic agents from these readily available seaweeds of Bangladesh. Dhaka Univ. J. Pharm. Sci. 22(1): 81-87, 2023 (June)